LEARNING AL QURAN HADITH AS THE BASIC FOUNDATION OF BUILDING THE MORALE OF LEARNERS AT MI MAKLUMUL MUKMININ NW PONDOK GEDANG - Muhammad Sufyan Ats-Tsauri; Siti Fatonah (Sunan Kalijaga International Journal on Islamic Educational Research, 2020)
The learning of the Qur'an Hadith was carried out by the subject teacher dimadrasah Ibtidaiyah NW pondok gedang designed with a concept that emphasizes more on the moral planting of children through the habituation of simple activities in school. This research uses descriptive qualitative research with the aim of describing the concept of student moral planting through the study of the Qur'an Hadith. From the results of this research shows that the teachers of the subjects of the Qur'an Hadith in madrasah ibtidaiyah menananmkan good habituation to students diantarranya is: 1). Habituation to say greetings. 2). Read basmallah to start the lesson. 3). Get along well with relatives in class. 4). throw the trash in the trash box. 5). When going into the classroom the teacher is used and emphasizes the habit of students to say hello. 6). when leaving the classroom is also used to say hello. 7). and teach adab in speech, learning ethics, eating ethics, drinking ethics, and so on. From this habituation, students' morals can be expected to be embedded both from elementary school age to college so as to provide positive implications to Religion, Nation and State.